The Intraocular Pressure under Deep versus Moderate Neuromuscular Blockade during Low-Pressure Robot Assisted Laparoscopic Radical Prostatectomy in a Randomized Trial. - Young-Chul Yoo; Na Young Kim; Seokyung Shin; Young Deuk Choi; Jung Hwa Hong; Chan Yun Kim; HeeJoon Park; Sun-Joon Bai (PLoS ONE)
Background This study aimed to determine whether continuous deep neuromuscular blockade (NMB) improves the surgical conditions and facilitates robotic-assisted laparoscopic radical prostatectomy (RALRP) under low intra-abdominal pressure (IAP) to attenuate the increase in intraocular pressure (IOP) during CO2 pneumoperitoneum in the steep Trendelenburg (ST) position. Methods Sixty-seven patients undergoing RALRP were randomly assigned to a moderate NMB group (Group M), including patients who received atracurium infusion until the end of the ST position, maintaining a train of four count of 1-2; and the deep NMB group (Group D), including patients who received rocuronium infusion, maintaining a post-tetanic count of 1-2. IOP was measured in all patients at nine separate time points. All RALRPs were performed by one surgeon, who rated the overall and worst surgical conditions at the end of the ST position. Results The highest IOP value was observed at T4 (60 min after the ST position) in both Group M (23.3 ± 2.7 mmHg) and Group D (19.8 ± 2.1 mmHg). RALRP was accomplished at an IAP of 8 mmHg in 88% Group D patients and 25% Group M patients. The overall surgical condition grade was 4.0 (3.0-5.0) in Group D and 3.0 (2.0-5.0) in Group M (P < 0.001). Conclusion The current study demonstrated that continuous deep NMB may improve surgical conditions and facilitate RALRP at a low IAP, resulting in significant attenuation of the increase on IOP. Moreover, low-pressure pneumoperitoneum, facilitated by deep NMB still provided acceptable surgical conditions. Trial registration ClinicalTrials.gov NCT02109133.